СНОВИДЕНИЯ КАК КОМПОНЕНТ ДУХОВНОЙ КУЛЬТУРЫ КОРЕННЫХ НАРОДОВ АМУРО-САХАЛИНСКОГО РЕГИОНА : DREAMS AS A COMPONENT OF SPIRITUAL CULTURE OF THE INDIGENOUS PEOPLES OF THE AMURO-SAKHALIN REGION - Каштанюк Валерия Александровна (Вестник Приамурского государственного университета им. Шолом-Алейхема, 2020)
Dreams play a big worldview role in the traditional and modern culture of the indigenous peoples of the Amur-Sakhalin region, namely Nanais, Negidals, Nivkhis, Orochis, Udeges, Uiltas, Ulchis, Evenkis. They are not only a source of specific information about real life, about its sacred aspects, but their interpretation can be used as recommendations for solving life problems of an individual person or society. : Dreams play a big worldview role in the traditional and modern culture of the indigenous peoples of the Amur-Sakhalin region, namely Nanais, Negidals, Nivkhis, Orochis, Udeges, Uiltas, Ulchis, Evenkis. They are not only a source of specific information about real life, about its sacred aspects, but their interpretation can be used as recommendations for solving life problems of an individual person or society.